The Legal Standing of Deepfake Digital Evidence in Criminal Proceedings: Challenges of Evidentiary Integrity in the AI Era - Adrian Bima Putra (Fox Justi : Jurnal Ilmu Hukum, 2026)
The rapid advancement of Artificial Intelligence (AI) has introduced deepfake technology, triggering a crisis of authenticity regarding criminal evidence. This study aims to analyze the legal standing of deepfakes within the Indonesian criminal justice system and the challenges of maintaining evidentiary integrity during trials. Employing a normative legal research method, this study examines the synchronization between technological developments and current positive law regulations. The results indicate that while the ITE Law recognizes electronic information and documents as valid legal evidence, the emergence of deepfakes poses an existential threat to the "seeing is believing" judicial paradigm. This technology is capable of manipulating visual and audio realities with high precision, making it increasingly difficult to distinguish from authentic recordings. These findings highlight a significant gap in digital forensic standards and judicial readiness in Indonesia. The lack of specific verification protocols risks the admission of fabricated evidence, which could ultimately undermine the pursuit of justice. The study concludes by emphasizing the urgent need for judicial procedural reforms and the establishment of specialized AI forensic protocols. Such measures are crucial to mitigate the risk of judicial errors and ensure that the legal system remains adaptive yet rigorous in safeguarding evidentiary validity in the era of digital disruption.